Microspheres: Technologies, applications and role in drug delivery systems - Fraceto, Leonardo Fernandes [UNESP]; de Araujo, Daniele Ribeiro (My University, 2014)
The book presents to the reader an interdisciplinary vision of microspheres including its concepts and applications. The book ranges from the preparation of microspheres using different methodologies (such as sol-gel processes) through different characterization techniques as well as the use of these systems for diagnostic diseases (cancer and hemodynamics fields). In addition, this book discusses aspects of the use of microspheres in: i) catalysis and separation sciences; ii) theoretical studies for applications in optical devices; iii) development of new systems aiming biomedical applications and iv) development of carrier systems for bioactive compounds. Thus this book covers a wide range of areas such as physics, chemistry, mathematics, biology, biomedical engineering, medical, and food, among others. This book presents new advances in the use of microspheres and, in this way, we intend to contribute to students, teachers, researchers, research centers, companies, and industries which have interest in these topics. The book is organized into eleven chapters written in a clear and concise form with illustrations that will help readers comprehend all subjects. Furthermore, this book will contribute to the generation of knowledge in this field.